2011
DOI: 10.3988/jcn.2011.7.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy Bodies versus Alzheimer's Disease and Parkinson's Disease Dementia: A Comparison of Cognitive Profiles

Abstract: Background and PurposeIt is particularly difficult to differentiate dementia with Lewy bodies (DLB) from the related dementias of Alzheimer's disease (AD) and Parkinson's disease dementia (PDD). Few studies have been designed to comparatively analyze detailed neuropsychological assessments of DLB patients and patients with AD and PDD.MethodsThree groups of patients participated in this study: 10 with DLB, 76 with AD, and 17 with PDD, who had been diagnosed as probable DLB, AD, and PDD, respectively, according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 30 publications
6
49
1
Order By: Relevance
“…Nevertheless, cognitive alterations in PD are now known to differ from those typical of neurodegenerative diseases of cortical predominance (Bronnick, Emre, Lane, Tekin, & Aarsland, 2007;Noe et al, 2004;Park et al, 2011). The current model for assessing PD also taps EFs, as these may be disrupted following fronto-striatal damage.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, cognitive alterations in PD are now known to differ from those typical of neurodegenerative diseases of cortical predominance (Bronnick, Emre, Lane, Tekin, & Aarsland, 2007;Noe et al, 2004;Park et al, 2011). The current model for assessing PD also taps EFs, as these may be disrupted following fronto-striatal damage.…”
Section: Discussionmentioning
confidence: 96%
“…Although neuropsychological deficits in PD have been clearly documented, the characteristic profiles based on disease duration and the underlying neuropathology implicated remain controversial [5,7,8]. This is especially the case when reviewing the literature on dopamine replacement therapy in cognition.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this was the first Chinese study that employed these biomarkers to achieve high accuracy of clinical diagnoses of AD, DLB, and FTD and then compared their clinical features. All previous Caucasian and Asian studies that reported or compared clinical features obtained dementia diagnoses without any biomarker support …”
Section: Discussionmentioning
confidence: 99%
“…A case series of 35 Chinese DLB patients noted memory impairment was found in 58.8% of the patients . A Korean study comparing clinically diagnosed DLB ( n = 10) and AD ( n = 76) patients found that these two groups of patient had a similar degree of impairment in three‐word recall and 20‐min delayed recall . The memory impairment in DLB patients was proposed to be the result of medial temporal lobe (hippocampus and amygdala) degeneration and encoding impairment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation